Identification of risk epitope mismatches associated with de novo donor‐specific HLA antibody development in cardiothoracic transplantation. Issue 12 (22nd June 2018) - McCaughan, J. A.; Battle, R. K.; Singh, S. K. S.; Tikkanen, J. M.; Moayedi, Y.; Ross, H. J.; Singer, L. G.; Keshavjee, S.; Tinckam, K. J.
Abstract : The development of de novo donor‐specific HLA antibodies (dnDSA) after transplantation is associated with graft failure, mortality, and cost. There is no effective therapeutic intervention to prevent dnDSA or ameliorate associated injury. The aims of this study were to identify specific HLA factors associated with dnDSA development and to propose primary prevention strategies that could reduce the incidence of dnDSA without prohibitively limiting access to transplant. The investigation cohort included heart transplant recipients from 2008 to 2015 (n = 265). HLA typing was performed and HLA antibody testing was undertaken before and after transplantation. HLAMatchmaker analysis was performed for persistent dnDSA to identify potentially more immunogenic eplet differences. Validation was performed in recipients of lung transplants from 2008 to 2013 (n = 433). The majority of recipients with dnDSA had antibodies to identical eplet positions on DQ2 and DQ7. A high‐risk epitope mismatch (found in DQA1*05 +  DQB1*02/DQB1*03:01(7)) was associated with a 4.2‐ and 4.9‐fold increased risk of dnDSA in heart and lung recipients respectively. HLA electrostatic potential modeling provided a plausible explanation for this observed immunogenicity. A theoretical allocation algorithm avoiding high‐risk epitope mismatches was generated and predicted to reduce dnDSA by up to 72% without additional testing, eplet analysis, or cost. Abstract : This study identifies HLA risk epitope mismatches, which were the stimulus for the majority of de novo donor‐specific antibodies in heart and lung transplant populations, and proposes a pragmatic prevention strategy to reduce donor‐ specific antibody development without additional testing, at no extra cost, and while maintaining access for potential recipients to the majority of donors. Wiebe et al's editorial is onpage 2845 .